Pendeteksian Kecurangan Laporan Keuangan Di Tinjau Dari Tekanan Waktu Dan Independensi - Faisal, Yusuf; Herdian, Bagas; Greentika, Gesika; Samela, Novi (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This study aims to examine the effect of time pressure and independence on the ability to detect financial statement fraud. This research was conducted at an independent prosperous cooperative. The sampling technique used was purposive sampling with predetermined criteria. The data used in this study is primary data in the form of questionnaires distributed to respondents. 60 questionnaires were distributed, 48 questionnaires were returned and were feasible to use and could be processed in this study. The research method used is a quantitative research method. The data were obtained by distributing questionnaires and measured using a Likert scale. The data analysis method uses multiple linear regression analysis which is processed through SPSS software. Based on the analysis that has been carried out, the result is that time pressure and independence have a positive effect on the ability to detect fraudulent financial reports.